Exhibition, Marketplace, and Handicraft Development Building in Jepara Regency with Neo- Vernacular Approach - Khirza Faiz Dzikrillah (Canopy: Journal of Architecture, 2023)
Jepara is known as the city of woodcarving. This reputation is attributed to the success of Jepara's carved furniture products in entering the international and global markets. In addition to woodcarving crafts, Jepara also produces various other crafts. The types of crafts in Jepara are diverse, including pottery, calligraphy, furniture, metalwork, sculptures, rattan weaving, batik, and woven textiles. These various crafts are concentrated in different areas within Jepara Regency. However, in its development, the number of craft practitioners in Jepara has decreased due to the development of several industrial areas in the regency, leading people to prefer working as factory employees rather than craftsmen. Therefore, efforts need to be made to preserve the crafts in Jepara as cultural heritage and potential for improving the community's economy in the creative industry sector. In this regard, the proposed solution is to establish an Exhibition, Marketplace, and Handicraft Development Building to preserve the crafts in Jepara as cultural heritage and economic potential in the creative industry sector. The Exhibition, Marketplace, and Handicraft Development Building can serve as educational facilities and economic activities related to crafts in Jepara Regency